OPTIMIZING MODERN AGRICULTURAL PRODUCTS THROUGH A DRIP IRRIGATION SYSTEM IN THE PAPUA FARM FARMERS GROUP, AIMAS REGENCY, SOUTHWEST PAPUA - Athirah, Aldila Mawanti; Aprianto, Aci; Sabarudin, Dian Nitari Ribanor; Risdianti, Tri Sindi; Suciati, Suciati; Mawar, Mawar; Badali, Muhammad Imam Mudin (LPPM Univ. Ibn Khaldun Bogor, 2025)
Increasing agricultural productivity in Eastern Indonesia, particularly in Aimas District, Sorong Regency, is a strategic step in supporting local food security and farmer welfare. Papua Farm, a pioneer in hydroponic lettuce cultivation in Papua, faces challenges such as limited water, climate fluctuations, and limited access to modern agricultural technology. A community service program titled